Method for the detection of smallsized air objects by observational radars - Khudov, Hennadii; Zvonko, Andrii; Kovalevskyi, Sergiy; Lishchenko, Vitaliy; Zots, Fedor (Eastern-European Journal of Enterprise Technologies, 2018)
We proposed the introduction of an additional mode of dispersed reception and the combination of one-position and multiple reception of signals to the existing one-position observation radar. We improved the algorithm for detection of an air object at its irradiation by several transmitters. We provided compensation of a delay time and Doppler frequency in each receiving channel to a separate volume of an observation radar upgrading the algorithm. The improved algorithm for detection of an air object at its irradiation by several transmitters is reduced to: coherent processing of received signals in each processing channel in each element corresponding to the relevant separate volume and the relevant separate Doppler frequency; quadratic detection in each processing channel in each element corresponding to the relevant separate volume and the relevant separate Doppler frequency; weight summation of detector outputs for each processing channel in each element corresponding to the relevant separate volume and the relevant separate Doppler frequency. We constructed a structural diagram of the detector of an air object at its illumination by several transmitters. Each receiving channel of a signal is a multichannel for distance and speed. The diagram provides reception, coherent processing of echo signals from third-party sources, compensation of delay and Doppler frequency differences relative to a separate volume of the observation radar and incoherent weight summation. We carried out estimation of the efficiency of detection of an air object at its irradiation by several transmitters. We established that the transition from a single-channel detection of an air object to the detection of an air object at the incoherent combination of two channels results in a significant shift of detection characteristics to the left. We selected the number of receiving channels to be combined. We established that it is most effective to combine two, at most three, reception channels. We constructed a structural diagram of channels that process echo signals of an observation radar by combining the methods of one-position and differential signal reception. For combining of one-position and dispersed location modes of observation radars, we provided complexing of corresponding digital reception devices and digital signal processing systems. The main principle underlying the combination of the mentioned receiving devices is the informational supplement without violating the standard modes of operation of observation radar.